Human Rights and Indigenous Linguistic Rights of Colombia - Oliveros Marín, Yuri Elena (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The purpose of the article is to contribute to the debate on human rights an approach to their relationship with linguistic rights in the indigenous peoples, based on the question: What is the relationship between human rights and linguistic rights in the villages? indigenous people of Colombia? The methodological design for the project takes, from anthropology, the ethnographic method, which has been used by the discipline to study the way in which norms, ideas and human rights discourses are addressed by social actors. It is evident that it is necessary to incorporate an intercultural knowledge dialogue into the debate. It is concluded that, although the native language is an essential part in defining an indigenous people, by historical situations not all peoples have retained their language, yet they must exercise their right to defend it.